Bilateral Femoral Neuropathy Due to Bilateral Iliopsoas Hematoma During Anticoagulation Therapy: A Case Report - Emel Ekşioğlu,; Aslıhan Sever,; Ece Ünlü,; Ajda Bal,; Aytül Çakcı, (Archives of Rheumatology, 2006)
Anticoagulation therapy is used for both therapeutic and prophylactic purposes that decreases the mortality and morbidity, but may lead to serious bleeding complications in some cases. One of these complications is femoral neuropathy that is an important clinical problem due to bleeding in iliopsoas muscle. Here we present a case that was diagnosed bilateral femoral neuropathy due to hematoma in iliopsoas muscles after anticoagulation therapy for deep vein trombosis. (Rheumatism 2006; 21: 73-5)